Howling for Justice: New Perspectives on Leslie Marmon Silko's Almanac of the Dead (Rebecca Tillett, ed.) - Warburton, Theresa (Transmotion, 2015)
Review of Howling for Justice: New Perspectives on Leslie Marmon Silko's Almanac of the Dead edited by Rebecca Tillett